(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study investigates risk management practices in four major private sector banks in Bangalore, India: Axis Bank, ICICI Bank, HDFC Bank, and Kotak Mahindra Bank. Using SPSS, we analyzed data on Credit Risk, Market Risk, Operational Risk, and Liquidity Risk from the year 2023. Descriptive statistics revealed varying risk profiles among the banks, with Axis Bank exhibiting the highest Credit Risk and HDFC Bank facing the greatest Market Risk. Correlation analysis showed strong positive relationships between Credit Risk, Market Risk, and Operational Risk, indicating interconnected risk factors. Regression analysis highlighted that Credit Risk and Market Risk significantly impact overall risk management effectiveness, while Operational Risk and Liquidity Risk play smaller roles. Visualizations such as bar charts and heatmaps provided additional clarity on risk distribution and correlations. The findings underscore the importance of managing Credit and Market Risks effectively to improve risk management practices and ensure financial stability.